Early Childhood Learning Process According to Ki Hadjar Dewantara's Approach - Ashari, Amelia Tri; Aprilia, Dinda; Pransiska, Dini; Suhaillah, Yusrah (Lembaga Riset Mutiara Akbar, 2023)
Early Childhood Education (PAUD) has an important role in the development and formation of children's character. One of the approaches used in PAUD learning is the KI Hadjar Dewantara approach. KI Hadjar Dewantara's approach is an approach that focuses on building children's character, including developing their potential and intelligence. This approach prioritizes hands-on experiences and games as effective learning tools. In early childhood learning with the KI Hadjar Dewantara approach, the teacher acts as a facilitator who encourages children to actively learn and be creative. Children are given the freedom to explore and express their ideas, so they can develop their creativity and independence. In addition, KI Hadjar Dewantara's approach also emphasizes the importance of character education, such as moral values, social attitudes, and concern for the environment. Children are taught to respect themselves, others and the environment through interesting and meaningful activities. By adopting the KI Hadjar Dewantara approach, early childhood learning becomes more fun, interactive, and child-centered. Children can develop positive skills and values ??that will help them in their daily lives and in the future